Group Guidance Gratitude Intervention Technique to Improve the Meaning of Life of Inclusive Students - Eka Sari Setianingsih; Arif Taufiq Dani Abdillah (Kuras Institute, 2026)
The existence of meaning of life is an aspect that plays a very important role in well-being and self-achievement, for inclusive students, physical limitations experienced directly or indirectly will cause various psychological problems to arise, including tending to have psychological problems such as feeling anxious, tending to withdraw from social circles, being apathetic and having a bad outlook on life on oneself. This study tested the ability of group guidance services with gratitude intervention techniques in improving the meaning of life of inclusive students, with the pre-experimental design method through four times of providing group guidance services with gratitude intervention techniques to inclusive students in Central Java, with the meaning of life questionnaire instrument and observation resulting in data on significant changes before and after treatment, namely the Z value of 2,731 with an Asymp Sig value = 0.000 <0.05, pretest of 85.4 and posttest 123.1. The results of the analysis indicate that Group Guidance with Gratitude Intervention Techniques effectively has significant effectiveness in improving the Meaning of Life of Inclusive students in Central Java.